Estimation of Genetic Parameters and Heterosis in Half-Crosses of Bread Wheat (Triticum Aestivum L.) - Hamada, Yasser Hamad (American Journal of Biology and Natural Sciences, 2025)
The study was conducted in one of the farmers’ fields affiliated to Kirkuk Governorate. The study included (10) genetic compositions of wheat introduced from the International Center for Agricultural Research in the Dry Areas (ICARDA) that were introduced in half-crosses and the parents and heterosiss were planted in a randomized complete block design (RCBD) with three replicates. Data were recorded for the traits (number of spikelets, number of grains per spike, number of spikelets per plant, weight of 100 grains, individual plant yield, biological yield, harvest index and yield efficiency). The analysis of variance showed that the mean squares of (parents), (heterosiss), (parents and heterosiss), (genotypes and parents, and parents against heterosiss and heterosiss) were significant at the probability level (1%) for all the studied traits under study except for the trait of number of spikelets, harvest index and yield efficiency, and parents against heterosiss for the trait of weight of 1000 grains and individual plant yield, in estimating the degree of dominance and heritability in the broad and narrow sense and the expected genetic improvement for all traits. The studied, as the values for all the traits showed no dominance in them except for the number of grains/spike, the harvest index and the efficiency of the crop. It is also noted that all the traits had a high degree of heritability in both the broad and narrow senses. The reason for the high heritability values for the above-mentioned traits is due to the high values of genetic variance compared to the environmental variance. Also, the values of the expected genetic improvement for the studied traits were low in all the traits except for the number of spikelets, the individual plant yield and the biological yield, which were average. The expected genetic improvement in the grain yield is the result of increasing one or more of the main components of the yield because it is the result of multiplying these components that form it. The presence of significant heterosis strength compared to the average of the parents as a percentage for most heterosiss and in all the traits indicates that the ability to combine was highly significant in the parents, which is passed on to their offspring. These results give the opportunity to predict the possibility of benefiting from these heterosiss directly because they possess the genes of the desired traits or introducing them into repeated selection programs to increase the frequency of certain desired genes to obtain a new variety with desirable traits.